Physical and numerical simulation of the coalescence of liquid inclusion particles in molten steel - CHEN Kai-lai; WANG De-yong; QU Tian-peng; TIAN Jun; WANG Hui-hua (工程科学学报)
In steelmaking process, nonmetallic inclusions are often considered to be detrimental to the mechanical properties and product quality of steel as they influence the microstructure of the steel matrix to a large extent, and thus, much industrial efforts are being made to promote inclusion removal by upward flotation. From this point of view, inclusions with large size are favorable; however, quality problems or mechanical defects are more likely to happen if some of them remain in the steel. In addition, fine nonmetallic inclusions can be utilized as nucleation sites of acicular ferrite during phase transformation to improve the steel strength by promoting the formation of a fine-grained structure; this procedure is known as oxide metallurgy. In both cases, the key issue is to control the size of inclusion particles. The main factor affecting inclusion size is the collision, agglomeration, and coalescence behavior of inclusions in the molten steel. Interfacial characteristics between inclusions and steel melts are known to have a significant influence on this coalescence behavior. To analyze this influence mechanism in depth, physical and numerical simulation methods were applied to investigate the effects of inclusion type, interfacial tension, and viscosity on droplet coalescence. Based on the similarity principle, water and organic reagents were chosen to simulate molten steel and liquid nonmetallic inclusions, respectively, in the physical modeling part. The results indicate that the coalescence tendency of inclusion droplets is closely related to the physical properties of the droplets. The interfacial tension between the droplet phase and the continuous phase promotes the mutual aggregation of droplets, while the viscosity of droplets plays an inhibitory role during the aggregation process. Therefore, it is feasible to achieve aggregation or dispersion of inclusions in liquid steel by changing interfacial or viscosity parameters, thereby realizing flexible control of the inclusions particle size.